2010
DOI: 10.1111/j.1755-263x.2010.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Global mismatch between research effort and conservation needs of tropical coral reefs

Abstract: Tropical coral reefs are highly diverse and globally threatened. Management to ensure their persistence requires sound biological knowledge in regions where coral reef biodiversity and/or the threats to it are greatest. This paper uses a novel text analysis approach and Google Maps TM to examine the spatial coverage of scientific papers on coral reefs listed in Web of Science R . Results show that research is highly clumped spatially, positively related to per capita gross domestic product, negatively related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 21 publications
3
116
0
Order By: Relevance
“…This supports previous studies that found GDP is posi- tively correlated with conservation science research effort (e.g. Lawler et al 2006, Fisher et al 2011 and in particular those which show that research effort on European bird species is biased towards Western Europe, which has a higher per capita GDP than Eastern Europe (Baldi & Batary 2011, Tryjanowski et al 2011. Countries with higher per capita GDPs are more likely to be able to invest in funding for conservation through government-sponsored research in universities and research institutes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This supports previous studies that found GDP is posi- tively correlated with conservation science research effort (e.g. Lawler et al 2006, Fisher et al 2011 and in particular those which show that research effort on European bird species is biased towards Western Europe, which has a higher per capita GDP than Eastern Europe (Baldi & Batary 2011, Tryjanowski et al 2011. Countries with higher per capita GDPs are more likely to be able to invest in funding for conservation through government-sponsored research in universities and research institutes.…”
Section: Discussionsupporting
confidence: 77%
“…Both analyses found that species classed in more globally threatened IUCN Red List categories received greater research effort than those in less threatened groups. In contrast, work on other taxonomic groups, such as Felidae (Brodie 2009) and coral reefs (Fisher et al 2011), did not show a relationship between research effort and threat status.…”
Section: Introductionmentioning
confidence: 75%
“…This phenomenon has previously also been observed in other fields of conservation biology (Trimble & van Aarde 2010, Fisher et al 2011). Farrier et al (2007) noted that, although classifying species as endangered is expected to result in appropriate prioritisation of activities and efforts, such as establishment of research priorities, other values and factors (e.g.…”
Section: Reasons For Lack Of Researchmentioning
confidence: 59%
“…Although our analysis did not identify strong relationships between knowledge and possible determinants other than geographic variation, a number of recognised factors might explain why some islands have received more attention than others including logistical constraints, such as ease of access due to geographic location (Hendriks and Duarte 2008;Jarić et al 2015), as well as financial ones such as island wealth (e.g. Fisher et al 2011). …”
Section: Discussionmentioning
confidence: 88%